An investigation into the impact of a community-based rehabilitation intervention strategy on persons with physical disabilities in an urban and rural setting in Zambia - Banda-Chalwe, M. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MMed)--Stellenbosch University, 2005.